He's Variational Iteration Method for Solving Fractional Riccati Differential Equation - H. Jafari; H. Tajadodi (International Journal of Differential Equations)
We will consider He's variational iteration method for solving fractional Riccati differential equation. This method is based on the use of Lagrange multipliers for identification of optimal value of a parameter in a functional. This technique provides a sequence of functions which converges to the exact solution of the problem. The present method performs extremely well in terms of efficiency and simplicity.